2009 International Conference on Computers &Amp; Industrial Engineering 2009
DOI: 10.1109/iccie.2009.5223889
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Hierarchy Process decision model for e-waste collection center location selection

Abstract: Electronic waste refers to thousands of discarded electronic devices such as computers, televisions, cell phones, and printers. Electronic waste streams are growing rapidly related to the growing sales and shortening the life spans of electronic products.The elements of reverse logistics for electronic products are collection, grading and sorting, re-processing and re-distribution. The success of the reverse logistics is strongly related with the collection activity and the collection activity is strongly rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Economic objectives (land costs, personnel costs, energy prices), infrastructural objectives (facility access, agglomeration effects, proximity to inhabited areas, absence of other E-WASTE recycling plants, availability of labor), and legal objectives (availability of a local waste processing programs, environmental grants) Thai and Grewal (2005) Proximity to customers' bases, availability and quality of labour workforce, availability of utilities, local tax environment, in land transport infrastructures, expansion capability, customs administration and regulations, local standards of living Turgut et al (2011) Cost, transportation, infrastructure, geographic location, suitability of climate Yang and Lee (1997) Access to markets/distribution centers and suppliers/resources, community/government access, competitive considerations, environmental factors, labour, taxes and financing, utilities services, transportation Yüksel (2009) Cost, common effect, access, facilities, legal arrangements, environment, and area …”
Section: Steps Of the Type-2 Fuzzy Topsis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Economic objectives (land costs, personnel costs, energy prices), infrastructural objectives (facility access, agglomeration effects, proximity to inhabited areas, absence of other E-WASTE recycling plants, availability of labor), and legal objectives (availability of a local waste processing programs, environmental grants) Thai and Grewal (2005) Proximity to customers' bases, availability and quality of labour workforce, availability of utilities, local tax environment, in land transport infrastructures, expansion capability, customs administration and regulations, local standards of living Turgut et al (2011) Cost, transportation, infrastructure, geographic location, suitability of climate Yang and Lee (1997) Access to markets/distribution centers and suppliers/resources, community/government access, competitive considerations, environmental factors, labour, taxes and financing, utilities services, transportation Yüksel (2009) Cost, common effect, access, facilities, legal arrangements, environment, and area …”
Section: Steps Of the Type-2 Fuzzy Topsis Methodsmentioning
confidence: 99%
“…1 is proposed for the e-waste reverse logistics location selection problem. The studies of Barker andZabinsky (2011), Gan (2010), Queiruga et al (2008) and Yüksel (2009) are used as a base for the suggested value hierarchy. The selection is made among five location alternatives (as seen at Fig.…”
Section: A Case Study In E-waste Recycling Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse logistics is upstream movement of goods from end users to OEM [17]. Srivastava [18] defined reverse logistics as a process to plan, implement, and control the flow of returned products in order to recover value [19]. In short, reverse logistics is a process of returning products from the end user to supplier.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently, majority of electronic products are being recovered by conventional means and repair/cannibalization industry is the largest source of electronic scrap collection from end users. As per environmental protection agency (EPA), "Professionals approximate a recovery of 24 kg (50 lb) of gold, 250 kg (550 lb) of silver, 9 kg (20 lb) of palladium, and more than 9,000 kg (20,000 lb) of copper from reprocessing 1 million cell phones" [19,20].…”
Section: Literature Reviewmentioning
confidence: 99%